Keratinocyte cancers in South Australia: incidence, geographical variability and service trends. (4th July 2018) - Adelson, Pamela; Sharplin, Greg R.; Roder, David M.; Eckert, Marion
Abstract: Objectives: To determine the incidence, multiplicity, geographical variability and service trends of keratinocyte cancers (KC) in South Australia (SA). Methods: Medicare Australia data with a unique identifier were used to assess the number of people treated over years 2010–2014. A maximum of one KC service claim per year was used to determine incidence. Age‐standardised rates were estimated as were KC service activity trends. Results: There were 497, 581 services to 204, 183 SA residents for KC, solar keratoses, locally aggressive skin tumours or suspicious skin lesions. Of these, n=159, 137 services were for KC (77, 502 people). The five‐year (2010–2014) age‐standardised rate of KC in SA was 1, 466.6 (95%CI 1, 458.3‐1, 474.8) per 100, 000. Forty per cent of people had more than one KC removed. Men accounted for more incident cases (59.2%). Age‐specific rates showed least variability over time in the youngest age group (15–44 years). For 26 geographical areas, higher age‐standardised ratios of KC were seen in coastal and agricultural areas. There was a 59% increase in services for KC from 2000 to 2015. Conclusions: Age‐standardised rates for KC are relatively stable in SA, but regional variations are evident. Services for KC continue to rise. Implications for public health: This is the first systematic report of KC in SA. We demonstrate the utility of using validated Medicare data for assessing KC incidence and trends.